Daily averaged physical parameters from the Multidisciplinary BASS Mesocosm Study at Wilhelmshaven, 2023 - Riaz Bibi; Mariana Ribas-Ribas; Leonie Jaeger; Carola Lehners; Lisa Gassen; Edgar Cortés; Jochen Wollschläger; Claudia Thölen; Hannelore Waska; Jasper Zöbelein; Thorsten Brinkhoff; Isha Athale; et al. (PANGAEA, 2025)
This dataset contains daily averaged physical and chemical parameters measured during a mesocosm experiment conducted at Sea Surface Facility (SUR) in Wilhelmshaven, Germany (53.5148°?N, 8.1461°?E) in 2023. Parameters include daily average air temperature, Daily Average Incoming Solar Irradiance, Daily Average Reflected Solar Irradiance, and Daily Average Albedo derived from in situ measurements. The dataset provides an overview of environmental conditions throughout the experiment, supporting the interpretation of biogeochemical and ecological processes described in the related publication Bibi et al., 2025.
In: Bibi, R et al. (2025): Physical, chemical, and biogeochemical parameters from a mesocosm experiment at the Sea Surface Facility (SURF), Wilhelmshaven, Germany, spring 2023 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984101